2023
DOI: 10.3390/ijms24129906
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Global Transcriptomic Profiles of Holstein Cows According to Parity Reveal Age-Related Changes in Early Lactation

Abstract: Cows can live for over 20 years, but their productive lifespan averages only around 3 years after first calving. Liver dysfunction can reduce lifespan by increasing the risk of metabolic and infectious disease. This study investigated the changes in hepatic global transcriptomic profiles in early lactation Holstein cows in different lactations. Cows from five herds were grouped as primiparous (lactation number 1, PP, 534.7 ± 6.9 kg, n = 41), or multiparous with lactation numbers 2–3 (MP2–3, 634.5 ± 7.5 kg, n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 131 publications
0
1
0
Order By: Relevance
“…Calcium also plays an important role in restoring the reproductive function of cows (Mahen et al, 2018;Cheng et al, 2023). Studies have shown that serum calcium drops 9 hours before birth and returns to the normal range about 72 hours after birth (Megahed et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Calcium also plays an important role in restoring the reproductive function of cows (Mahen et al, 2018;Cheng et al, 2023). Studies have shown that serum calcium drops 9 hours before birth and returns to the normal range about 72 hours after birth (Megahed et al, 2018).…”
Section: Discussionmentioning
confidence: 99%